AKTULALISASI PEMBELAJARANBERPUSAT PADA SISWA SMA DJ KABUPATENKLATEN - Bambang Subali (LPMPP Universitas Negeri Yogyakarta, 2008)
The objective of this researchis to evaluate of the quality of internationalstandard schools (in Indonesia called SB/) and national standard schools (SSN) ofsenior high schools compared to other senior high schools categorized as neitherSBI nor SSN located in'Klaten. The evaluation focused on goal-oriented evaluationof thetwo issues: (1) teachers' attempts to deal with student-centred teaching andlearning activities and .(2) teachers' attempts to encourage their students to learn.This researchwas conducted at SMAN 1 Klaten (SB1), SMA 2 Klaten (SSN),SMANJogart lan andSMAN Prambanan, which is neither SBI nor SSN. To obt in thedata, two sets of questionnaires were administered.'To triangulate and to slipportdata collection, interviews with,the principals of, the four schools were cOlducted.'To satisfy the validity and the reliability of the interpretation of data, theinstruments,'weredeveloped.on the basis of blueprints and empirically analyzepusing QUEST. The obtaiRed data were analyzed with a descriptive analysis. Withregard to the data analysis; the results reveal that thereis only a slight differenceiptermsof the two issues above between schools' categorized as SBland' SSNcomparedtoctwo other schools categorized as neitherSBJ nor SSN